EVALUASI VENDOR SEMEN BERDASARKAN METODE ANALYTIC HIERARCHY PROCESS (AHP) PADA PROYEK KONSTRUKSI CV YPP - Fadly Rizky Dermawan; Ririn Novitasari Pakpahan; Rafly Fadhilah Arifan; Muchammad Fauzi (Universitas Widyatama, 2025)
Vendor selection is a strategic aspect that directly influences the success of operational activities in construction projects, especially in the procurement of primary materials such as cement. This study aims to provide an objective recommendation in determining the best cement vendor for CV YPP using the Analytical Hierarchy Process (AHP) method. Four main criteria analyzed include price, product quality, distribution distance, and compliance with contract specifications. Data were collected through questionnaires from project managers, procurement teams, and logistics personnel, then analyzed using the Super Decisions software. The results show that product quality holds the highest weight in the decision-making process. Vendor A achieved the highest global priority score (0.512), indicating it as the most optimal alternative for cement procurement. This study confirms that the AHP method can provide a systematic and measurable framework to support effective and efficient vendor selection decisions.